2015
DOI: 10.12659/ajcr.894443
|View full text |Cite
|
Sign up to set email alerts
|

An Autopsy Case of Rapidly Progressing Spindle Cell Carcinoma of the Lung Accompanied with Intratumor Hemorrhage

Abstract: Patient: Male, 74Final Diagnosis: Spindle cell carcinoma of the lungSymptoms: —Medication: Pemetrexed • carboplatinClinical Procedure: Biopsy and autopsySpecialty: OncologyObjective:Rare diseaseBackground:Spindle cell carcinoma (SPCC) of the lung is a subset of sarcomatoid carcinoma. Its clinical features are unclear because of its rarity. Here, we report an autopsy case of SPCC and review CT findings and chemotherapeutic regimens based on previous reports of this disease. To our knowledge, this is the first r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…All forms of SC have a low incidence, and PSCC is very rare, accounting for only 0.2% to 0.3% of all lung cancers. [ 6 ] We reviewed the PSCC case reports published in English, [ 4 , 6 11 ] and our present case, and summarized the clinical features of PSCC (Table 1 ). A total of 11 cases were analyzed, including 6 men and 5 women.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…All forms of SC have a low incidence, and PSCC is very rare, accounting for only 0.2% to 0.3% of all lung cancers. [ 6 ] We reviewed the PSCC case reports published in English, [ 4 , 6 11 ] and our present case, and summarized the clinical features of PSCC (Table 1 ). A total of 11 cases were analyzed, including 6 men and 5 women.…”
Section: Discussionmentioning
confidence: 99%
“…In all 5 PSCC cases with CT scan images, central, low-density regions were found in the lesions, which might be the most specific imaging feature of PSCC. Kida et al [ 4 ] suggested that this feature was related to hemorrhage at the center of the lesion. Five patients had involvement in the pleura or other distal organs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unique clinical and pathological characteristics and prognosis have seldom been illustrated yet. Even diagnosed at the early stage, PSCC showed an unsatisfied prognostic outcome (1)(2)(3). Lung biopsy is crucial for the patients suffered from PSCC, due to the incompletion of preoperative diagnosis under most circumstances.…”
Section: Introductionmentioning
confidence: 99%